Beginner's guide to garden planning and design : 50 simple gardening ideas for adding style & personality to your outdoor space - Yoest, Helen (Creative Homeowner Press, 2024)
In the foreword of Planning & Designing Your First Garden: 50 Ways to Add Style for Personal Creativity, P. Allen Smith states, "Helen has outlined 50 ways to add style to express one's personal creativity in the garden--when in fact her 50 will inspire at least 50 more ideas." Rather than force her own creative ideas on you, author, gardener, and horticulturalist, Helen Yoest teaches you how to recognize and act on your own creativity. Sections include Garden Basics, Garden Styles, Garden Elements and Your Garden Environment. Learn about the importance of carving out the perfect space for your needs, how to create rhythm, scale, and balance along with curb appeal to help personalize your space, creating a sustainable garden environment where plants and animals can live together.